Rate of force development and maximal force: reliability and difference between non-climbers, skilled and international climbers - Levernier, G.; Laffaye, G. (Sports Biomechanics, 2021)
The goal of this study was to assess (i) test-retest reliability between sessions and within sessions, and (ii) the difference among three skill levels (international n = 12, skilled n = 10 and non-climbers n = 9) for finger flexor maximal force (Fmax) and rate of force development (RFD) at different time scales. Each climber performed a maximal finger flexion on a dynamometer in two different conditions: half crimp and slope crimp. The inter-session revealed no difference with low to high correlation from 0.56 to 0.94. Intra-session reliability reveals intraclass correlation ranging from 0.40 to 0.98 for all groups. The coefficients of variation ranged from 7.77% to 28.34% for RFD and 2.90% to 9.99% for Fmax. Maximal force, expressed as an absolute or normalised value, reveals a significant difference between all samples (22.11% difference between international and 38.58% between skilled and non-climbers). Finally, the difference in RFD200ms and RFD95% among the three groups suggests that the practice of intensive climbing causes many changes in neural and structural factors. Last, RFD200ms and RFD95% are highly reliable and can be used to discriminate samples, suggesting that these variables could be used in monitoring training.